ANALYSIS OF THE CONDITIONS AND ACTIVITIES PERFORMED IN DCC XXIV-SOFIA DURING THE 2011-2015 PERIOD - Anton Koychev; Tsvetelina Мihailova; Svetoslav Garov; Desislava Тоdorova (Peytchinski Publishing, 2016)
The adoption of the Health Insurance Act and the Health Act has resulted in setting up a contract based health insurance system in payment and delivery of medical services in Bulgaria. The health care reform has had a positive effect on outpatient care facilities such as the Diagnostic and Consultation Centers (DCC). The goal of the research is to analyze the activities performed in DCC XXIV-Sofia EOOD, focusing on the human, material and financial resources. Performance indicators, profitability and financial independence ratios have been calculated in order to prepare a financial and economic analysis of the activities. A thorough analysis of each resource flow would enable the management of DCC XXIV-Sofia EOOD to find ways of attracting funds through cash flow efficient management and entering into appropriate contracts in compliance with Bulgarian legislation.